Про деякі аспекти участі науковців НАН України у мінімізації наслідків Чорнобильської катастрофи - Барановська, Н.П. (Інститут історії України НАН України, 2009)
The article is dedicated to very important aspects of the researchers’ of scientific institutes of the National Academy of Sciences of Ukraine participation in solution of a wide range of problems which appeared due to the Chornobyl’ disaster, in ensuring Kyiv’s activity and in community health care.